RISPERIDONE IN INDIAN PATIENTS WITH SCHIZOPHRENIA - Agarwal, A.K. (Medknow Publications, 1998)
Conventional antipsychotic agents are not effective against negative symptoms of schizophrenia and are also noted for their extrapyramidal side effects. Risperidone is a noval antipsychotic agent whose dual antagonism of dopamine and serotonin receptors is believed to underlie its efficacy against negative symptoms and the low incidence of extrapyramidal side effects. An open, non-comparative study of seven weeks duration was performed to evaluate risperidone in the treatment of schizophrenia in Indian patients. Previous antipsychotic therapy was discontinued for a week before risperidone therapy was initiated. At the end of six weeks of risperidone therapy, clinical improvement (≥ 20% reduction in total score on positive and negative syndrome scale for schizophrenia (PANSS;; was shown by 128 (87.7%) of the 146 evaluable patients. Statistically significant reduction (p < 0.05) occurred in the total score of this scale and in the subscale scores for positive, negative and general psychopathology symptoms and in the clinical global impression severity score. The number of patients with adverse experiences were 108 (65.5%) at baseline and 120 (72.7%) at the end of risperidone therapy. Extrapyramidal symptoms, seen in 65 (39.4%) patients compared to 22 (13.3%) patients at baseline, were largely mild to moderate in intensity.